Will Bid/No-Bid Decision Factors for Construction Projects Be Different in Economic Downturns? A Chinese Study - Wang, Jinxiu; Wang, Lin; Ye, Kunhui; Shan, Yongwei (Applied sciences, 2020)
Whether to bid on construction work is a traditional question that is often challenged in different economic situations. What will the decision factors be when contractors have to struggle to achieve growth in economic downturns? Since previous studies have not widely agreed with each other on this issue, this study aims to examine China’s construction engineering contractors in recent “bad” years. The research findings reveal that the cluster related to expected profitability, including terms of payment, reputation of the client regarding his/her commitment to making timely payments, original price estimated by the client, profit track record for similar projects, and contract type, were the most significant determinants. The bid/no-bid decision-making process comprises three modules, including the contractor’s strategies, the contractor’s competency for a project, and expected competition. These results suggest that competing for survival is the dominant position of contractors in making bid/no-bid decisions in economic downturns.